2021
DOI: 10.1021/acsami.1c13429
|View full text |Cite
|
Sign up to set email alerts
|

Disclosing the Origin of Transition Metal Oxides as Peroxidase (and Catalase) Mimetics

Abstract: Since Fe 3 O 4 was reported to mimic horseradish peroxidase (HRP) with comparable activity (2007), countless peroxidase nanozymes have been developed for a wide range of applications from biological detection assays to disease diagnosis and biomedicine development. However, researchers have recently argued that Fe 3 O 4 has no peroxidase activity because surface Fe(III) cannot oxidize tetramethylbenzidine (TMB) in the absence of H 2 O 2 (cf. HRP). This motivated us to investigate the origin of transition metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 42 publications
1
43
0
Order By: Relevance
“…To confirm this correlation, dimethyl-1-pyrroline N-oxide (DMPO) was employed as a radical trap since it forms DMPO-OH with 1 : 2 : 2 : 1 resonance intensity in electron paramagnetic resonance (EPR). [32] As shown in Figure 3e, the amount of OH radicals produced among CeO 2 shapes are indeed associated with the electron density of their surface Ce species in the order of cube > sphere > octahedron (i. e., the opposite order of their Lewis acidity, Figure 2e). Interestingly, negligible OH radical was produced on octahedron CeO 2 , suggesting that the redox property of surface Ce species is also highly facet-dependent.…”
Section: An Insight Into the Specificity In Pod-like Reactionmentioning
confidence: 75%
See 1 more Smart Citation
“…To confirm this correlation, dimethyl-1-pyrroline N-oxide (DMPO) was employed as a radical trap since it forms DMPO-OH with 1 : 2 : 2 : 1 resonance intensity in electron paramagnetic resonance (EPR). [32] As shown in Figure 3e, the amount of OH radicals produced among CeO 2 shapes are indeed associated with the electron density of their surface Ce species in the order of cube > sphere > octahedron (i. e., the opposite order of their Lewis acidity, Figure 2e). Interestingly, negligible OH radical was produced on octahedron CeO 2 , suggesting that the redox property of surface Ce species is also highly facet-dependent.…”
Section: An Insight Into the Specificity In Pod-like Reactionmentioning
confidence: 75%
“…Surface Ce species with higher electron density should thus promote this step for oxidation of the OPD here (Figure 3d). To confirm this correlation, dimethyl‐1‐pyrroline N‐oxide (DMPO) was employed as a radical trap since it forms DMPO‐OH with 1 : 2 : 2 : 1 resonance intensity in electron paramagnetic resonance (EPR) [32] . As shown in Figure 3e, the amount of OH radicals produced among CeO 2 shapes are indeed associated with the electron density of their surface Ce species in the order of cube>sphere>octahedron (i. e., the opposite order of their Lewis acidity, Figure 2e).…”
Section: Resultsmentioning
confidence: 99%
“…Fe 3 O 4 nanoparticles are one of the most studied peroxidase nanozymes. Recently, Peng and co-workers investigated the origin of the peroxidase-like activity of Fe 3 O 4 nanoparticles and other transition-metal oxides by dissecting the surface reactions into the following steps: hydroxyl radical (OH•) and hydroperoxyl radical (HO 2 •) generation, chromogenic substrate oxidation, and surface active-site regeneration (Figure A) . By employing techniques such as H 2 -temperature-programmed reduction, O 2 -temperature-programmed oxidation, and electron paramagnetic resonance (EPR) spectroscopy, it was discovered that the redox reaction between the surface metal cation (oxidation) and H 2 O 2 (reduction) was the rate-limiting step for the catalytic activity.…”
Section: Metal Oxides As a Peroxidase Nanozymementioning
confidence: 99%
“…Using inorganic catalysts to convert enzyme substrates such as glucose, TMB (3,3′,5,5′-tetra­methyl­benzidine), and DNA to enzymatic reaction products (e.g., gluconic acid plus H 2 O 2 , oxidized TMB, and cleaved DNA, respectively) has been extensively studied since the discovery of the peroxidase-like activity of Fe 3 O 4 nanoparticles . Such nanoparticles are called peroxidase nanozymes because the same products as horseradish peroxidase (HRP) were generated, although they likely have distinct reaction mechanisms. , On the basis of the current status of the field, nanozymes are defined by their substrates and products instead of structural or mechanistic features . With obvious advantages in cost and stability, nanozymes have been used to replace enzymes for therapeutic applications, design of bioanalytical sensors, and degradation of environmental pollutants. …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the authors suggested that the reported catalytic activity was likely assigned to metal impurities from home-made magnetite particles. A recent study by Peng research group [21] shed light in the peroxidase mimic mechanism of metal oxides. In brief, the authors proved that the key step of the reaction was the fact that the redox between the particles surface ions Mn + (oxidation) and H 2 O 2 (reduction) generated OH radicals, which oxidize not only 3,3 0 ,5,5 0 -tetramethylbenzidine (TMB) for color change but also H 2 O 2 to produce HO 2 radicals for Mn + regeneration.…”
Section: Introductionmentioning
confidence: 99%